Critical Gaps at Unsignalized Intersections with Bending Right-of-Way - Kocianova, Andrea; Pitlova, Eva (Communications - Scientific letters of the University of Zilina, 2018)
The capacity calculation procedure for unsignalized intersections is based on the gap-acceptance theory in most of existing capacity regulations and it relies on one of the important parameters - critical gap. However, the capacity calculation procedure and values of critical gaps according to these regulations are valid only for intersections with standard right-of-way (major street leading straight). Nevertheless, in Slovakia, intersections with bending right-of-way (major street not leading straight, but bending) can be encountered. The specific mode of right-of-way results in different priority ranks of traffic movements (set by traffic rules of driving), more complicated traffic situation and therefore, different driver behaviour characteristics. To examine the gap acceptance behaviour of drivers under these specific conditions, an unsignalized four-leg intersection with bending right-of-way located in an urban area of Zilina, Slovakia, was selected. Three different methods (Raff, Wu, and MLM Troutbeck) were used for critical gap estimation from the field data. In the article, results of critical gaps for three through movements of different priority rank (major-street through movement of Rank 2 and minor-street through movements of Rank 3 and 4) are presented. The results show, that the values of critical gaps differ depending on the method by about 3-5 % only, which is not significant. Troutbeck ´s MLM method gives the highest values. The priority rank of movement has the greatest impact on the result. The values of critical gap for major-street through movement of Rank 2 are the smallest; they are approximately 1.3-2.1 s smaller than the values for minor-street through movements of Rank 3 or 4. The highest values of critical gap have been estimated for minor-street through movement of Rank 4 and they are higher compared to the current Slovak regulations TP 102 values for the same priority rank.